Information needs of rural health professionals: a review of the literature - Dorsch, J L (Bulletin of the Medical Library Association, 2000)
This review analyzes the existing research on the information needs of rural health professionals and relates it to the broader information-needs literature to establish whether the information needs of rural health professionals differ from those of other health professionals. The analysis of these studies indicates that rural health practitioners appear to have the same basic needs for patient-care information as their urban counterparts, and that both groups rely on colleagues and personal libraries as their main sources of information. Rural practitioners, however, tend to make less use of journals and online databases and ask fewer clinical questions; a difference that correlates with geographic and demographic factors. Rural practitioners experience pronounced barriers to information access including lack of time, isolation, inadequate library access, lack of equipment, lack of skills, costs, and inadequate Internet infrastructure. Outreach efforts to this group of underserved health professionals must be sustained to achieve equity in information access and to change information-seeking behaviors.